BRINE SHRIMP TERATOGENIC SCREENING TEST ON SOME SELECTED PLANTS - Lestari, Meti Widiya; Fidrianny, Irda; Yusuf, Ayda T; Soemardji, Andreanus A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: The aims of this research were to analyze teratogenic properties on some selected plants which often used for woman's health were pomegranate (Punica granatum L.) pericarp, coriander (Coriandrum sativum L.) seeds, liman (Elephantopus scaber L.) leaves, fennel (Foeniculum vulgare M.) seeds, and kaempferia (Kaempferia galanga L.) rhizomes using brine shrimp teratogenic screening test (BSTST) method. Methods: Artemia cysts were hatched into first stage nauplii then taken and put into seawater medium which contain test substance and kept alive until the second stage, third stage, and fourth stage and then observed number of deaths, morphological abnormalities, body length, and retarded of development for each stage. Results: Hatchability of cysts in fennel seeds compared extracts 1 and 0.5 mg/ml, coriander seeds extract 1 mg/ml, pomegranate rinds extract 6 mg/ml, and liman leaves extracts 6, 3, and 1.5 mg/ml were significantly different to control (p<0.05). Survival nauplii in fennel seeds extracts 1 and 0.5 mg/ml and liman leaves extracts 6 and 3 mg/ml were significantly different to control (p<0.05). The morphological abnormalities were exposed on coriander seeds extract 1 mg/ml, liman leaves extract 6 mg/ml, and pomegranate rinds extract 3 mg/ml. Nauplii with retarded development were presented on fennel seeds extracts 1 and 0.5 mg/ml, coriander seeds extracts 1 and 0.25 mg/ml, pomegranate rinds extracts 6, 3, and 1.5 mg/ml, and liman leaves extracts 3 and 1.5 mg/ml. Nauplii body length on plants extract showed no significantly difference compared to control. Conclusion: Based on BSTST, fennel seed and pomegranate rind extracts had no teratogenic effect, kaempferia rhizomes act as larvicide its analog in mamalia as embryo lethal, while coriander seeds and liman leaves extracts potentially had teratogenic properties.